Neoadjuvant chemotherapy outcome with taxane-based versus non-taxane protocols in gastric cancer - Shirin Kianersi; Sina Salari; Hamid Rezvani; Mohammad A Araskhan; Alireza Shirangi; Mohammad R Fathi; Mahmoud D Ghorbi (Journal of Education and Health Promotion, 2023)
BACKGROUND: Gastric cancer is the fifth most common cancer worldwide. One of the chemotherapy agents, taxanes is important in increasing patients' survival. The purpose of this study is to assess the efficacy of taxane-based drugs versus non-taxanes in neoadjuvant chemotherapy in non-metastatic gastric adenocarcinoma (GA) in Iranian patients. MATERIALS AND METHODS: In a historical cohort method, 65 patients between 18 and 75 years old who suffered from non-metastatic GA were included. Nineteen and 21 and 25 patients, had undergone DCF (docetaxel, cisplatin, 5fluorouracil) and FLOT (5fluorouracil, leucovorin, oxaliplatin, docetaxel) and FOLFOX6 (oxaliplatin, leucovorin, 5fluorouracil) regimens, respectively, between 2018 and 2021. Survival criteria consisting of progression-free survival (PFS), overall survival (OS), progression rate, and mortality rate were evaluated using the Kaplan–Meier method, in a three-year follow-up period. RESULTS: The majority of patients were male (72.3%), with a median age of 65 years. Most of the patients had lesions with tumor, node, metastasis (TNM) stage IIIb (27.7%) and poor differentiated pathological grade (49.2%). OS time had a significant correlation with the low TNM stage (P = 0.01), well-differentiated pathological grade (P = 0.005), and FLOT vs. FOLFOX protocol (20.3 vs. 12.2 months, respectively. P =0.04). FLOT regimen had significantly better OS survival vs. DCF regimen (20.3 vs. 15.4 months, respectively, P = 0.03). No significant correlation was observed between survival criteria and other factors like gender, age, past medical history, Karnofsky scale, and tumor location in the stomach. The taxane-based arm (sum of DSF and FLOT) had no superiority over the non-taxane arm in survival criteria. CONCLUSION: FLOT protocol, as a taxane-based regimen had better survival compared to FOLFOX protocol in neoadjuvant chemotherapy in gastric non-metastatic adenocarcinoma.